Insufficient physical activity and multimorbidity was associated with low physical functional performance in older adults: a cross-sectional study - Clóvis Arlindo de Sousa; Ana Paula Floriani; Sabina Ulbricht; Ulrike Siewert-Markus; Jennis Freyer-Adam; Till Ittermann; Henry Völzke; Marcus Dörr; Marcello Ricardo Paulista Markus; Ernani Tiaraju de Santa Helena (Brazilian Society of Geriatrics and Gerontology, 2022)
Objective: Aging, physical inactivity, and chronic disease can decrease strength and muscle mass and affect mobility and autonomy in older adults. This study aimed to analyze the prevalence and associated factors of low physical functional performance among older adults in the city of Pomerode, in southern Brazil. Methods: This is a cross-sectional population-based study with data on 733 older adults from the Study of Health in Pomerode - SHIP-Brazil. Low functional physical performance was defined as handgrip strength ≤ 32 kg for men or ≤ 20 kg for women and/or a Timed Up and Go test ≥ 11 seconds for men or ≥ 13 seconds for women. Associations were analysed by multiple logistic regression. Results: The prevalence of low physical functional performance was 43.7% (42.2% among women and 45.5% among men). Low physical functional performance was associated with the 70-79 years age group (odds ratio [OR] = 2.07) and insufficient physical activity (OR = 2.73) in men, and with the 70-79 years age group (OR = 2.09) and multimorbidity (OR = 1.87) in women. In general, older age, insufficient physical activity, and multimorbidity were associated with low physical functional performance in older adults. Conclusion: Our findings suggest that while insufficient physical activity is crucial for physical functional performance in older men, multimorbidity appears to be crucial for older women.